Isolation of thermotolerant Bacillus subtilis DCH4 from Chancos hot spring (Carhuaz, Peru) with potential to degrade lignocellulosic agriculture wastes - Tamariz-Angeles, Carmen (2020)
It was isolated bacteria strains from three different types of samples: fresh water, in situ baits and ex situ enrichment. Serial dilutions were prepared and culture was carried at 50 °C using a Basal-Saline medium. Isolated strains were screened for endoglucanase and xylanase activities with qualitative (Congo Red) and quantitative (DNS) methods. Molecular 16S rDNA sequencing analysis was performed for taxonomic identification. It was isolated 31 strains of which 14 showed hydrolytic activities and belonged to Bacillus subtilis and Bacillus licheniformis species. Moreover, the strain B. subtilis DCH4 showed the highest endoglucanase activity at 45°C and pH 5, and xylanase activity at 55°C and pH 6. Then, DCH4 was cultivated by submerged fermentation with two different media supplemented with sugar cane bagasse, wheat straw, or quinoa stalk to evaluate its saccharification capability. Likewise, it was screening its xylanase and cellulase genes employing specific primers; the amplicons obtained were sequenced, and analyzed. It was found that, enzymatic extracts of DCH4 prepared with cane bagasse or quinoa stalk media achieved the highest endoglucanase and xylanase activities. According to molecular analysis of genes involved in the hydrolytic process, the endoglucanase and xylanase activities exhibited by DCH4 could be attributed to a bifunctional cellulase conformed by endo-beta-1,4-glucanase (GH5) joined to cellulose binding domain 3 (CBM3), and an endo-1,4-beta-xylanase (GH11), respectively. Further transcriptomic experiments would be considered to accomplish optimization strategies for biofuel production from lignocellulosic biomass.